New high yielding seedless citrus variety ’Pusa Arun’ - Dubey, A K; Sharma, R M; Awasthi, O P; Singh, Awtar; Kaur, Charanjit (Indian Horticulture, 2020)
New high yielding seedless citrus variety ’Pusa Arun’